Determinasi Perilaku Menabung melalui Literasi Keuangan, Inklusi Keuangan, dan Pendapatan: Bukti Empiris dari UNPAZ Timor-Leste - Leto, Longuinhos Armando Silveira Idalina; Iramani, Iramani (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The study analyzes the impact of financial literacy, financial inclusion, and income levels on the savings behavior of lecturers and staff at the University of Paz (UNPAZ) in Timor-Leste. The methodology used was quantitative, with a survey conducted on 120 respondents selected through proportional random sampling. Data were analyzed using structural equation modeling–partial least squares (SEM-PLS). The results showed that financial inclusion and income substantially influence savings behavior, although financial literacy did not have a significant effect. These findings indicate that in addition to financial knowledge, structural and economic variables such as access to financial services and income significantly influence savings behavior. These findings emphasize the importance of increasing financial inclusion by facilitating access to formal financial services as a more effective and sustainable approach to encouraging savings behavior.